Ascites Due To Pseudomyxoma Peritonei (Pmp): A Rare Case Report - Ferdinal Ferry; Puti Fajri Lestari; Syamel Muhammad (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Pseudomyxoma Peritonei (PMP), also known as "jelly-belly," is a rare condition characterized by the accumulation of mucinous ascites in the peritoneal cavity. It often originates from mucinous neoplasms of the appendix and presents with non-specific symptoms like abdominal bloating and discomfort. Diagnosis is often incidental through imaging, surgery, or histopathology. Objective: To report the diagnosis and management of PMP in a 53-year-old woman presenting with abdominal enlargement. Case Report: A 53-year-old woman was referred with a two-month history of abdominal enlargement. Initial ultrasound findings suggested ascites due to cirrhosis or ovarian carcinoma. However, further evaluation with abdominal CT revealed ascites and cholelithiasis without signs of cirrhosis or ovarian carcinoma. Diagnostic laparoscopy showed peritoneal carcinomatosis, and 8000 ml of hemorrhagic ascites was drained. Histopathological examination confirmed the diagnosis of PMP, and tissue resection was performed. Conclusion: The management of PMP requires a comprehensive diagnostic approach, incorporating clinical history, physical examination, imaging, and histopathological evaluation. This systematic approach is crucial for accurate diagnosis and effective treatment of PMP.